Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas IV SD Negeri Manembo - Mayske R. Liando; Risal M. Merentek; Dini C. Tambayong (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this classroom action research is to improve students' ability to apply Indonesian language learning knowledge on short stories by implementing the Cooperative Integrated Reading and Composition model in grade IV of SDN 2 Manembo. The number of students in grade IV is 14 people. This research uses a classroom action research (CAR) method based on the inquiry learning method according to Kemmis and McTaggart (Aqib Zainal, 2016:64) and is implemented in two cycles. Each cycle consists of four stages, namely planning, action implementation, observation, and reflection. Qualitative data collection techniques are carried out through observation of learning activities, while quantitative data are collected from the results of LKPD. The data analysis technique uses the formula (Trianto, 2019:41) KB = T/Tt × 100%. Student learning outcomes in cycle I reached an average value of 70% with incomplete criteria, but increased in cycle II to 92% with complete criteria. In addition to improving learning abilities, students also feel more enthusiastic and active in participating in learning by implementing the Cooperative Integrated Reading and Composition model. It can be concluded that the implementation of the Cooperative Integrated Reading and Composition (CIRC) model can improve the reading comprehension skills of fourth-grade elementary school students.